A Rapid Method of Assessing the Photocatalytic Activity of Thin TiO2 Films Using an Ink Based on the Redox Dye 2,6-Dichloroindophenol - Andrew Mills; Mark McGrady; Jishun Wang; James Hepburn (International Journal of Photoenergy)
An indicator ink based on the redox dye 2,6-dichloroindophenol (DCIP) is described, which allows the rapid assessment of the activity of thin, commercial photocatalytic films, such as Activ. The ink works via a photoreductive mechanism, DCIP being reduced to dihydro-DCIP within ca. 7.5 minutes exposure to UVA irradiation of moderate intensity (ca. 4.8 mW cm−2). The kinetics of photoreduction are found to be independent of the level of dye present in the ink formulation, but are highly sensitive to the level of glycerol. This latter observation may be associated with a solvatochromic effect, whereby the microenvironment in which the dye finds itself and, as a consequence, its reactivity is altered significantly by small changes in the glycerol content. The kinetics of photoreduction also appear linearly dependent on the UVA light intensity with an observed quantum efficiency of ca. 1.8×10−3.